HAT1/HDAC2 mediated ACSL4 acetylation confers radiosensitivity by inducing ferroptosis in nasopharyngeal carcinoma - Peijun Zhou; Xingzhi Peng; Kun zhang; Jin Cheng; Min Tang; Lin Shen; Qin Zhou; Dan Li; Lifang Yang (Cell Death and Disease)
Abstract Protein acetylation modification plays important roles in various aspects of tumor progression. Ferroptosis driven by lethal lipid peroxidation is closely related to tumor development. Targeting ferroptosis has become a promising strategy. However, the crosstalk between protein acetylation and ferroptosis remains unclear. In present study, we found that the acetylation of acyl-CoA synthase long-chain family member 4 (ACSL4) enhances its protein stability and a double-edged sword regulation in nasopharyngeal carcinoma (NPC). On the one hand, ACSL4 could promote the malignant progress of tumors; on the other hand, it enhanced radiosensitivity by endowing NPC cells with ferroptosis-sensitive properties in vitro and in vivo. Mechanistically, histone acetyltransferase 1 (HAT1) directly promotes the acetylation of ACSL4 at lysine 383, and deacetylase sirtuin 3 (SIRT3) mediates the deacetylation of ACSL4. Meanwhile, another deacetylase histone deacetylase 2 (HDAC2) enhances ACSL4 acetylation through inhibiting the transcription of SIRT3. Acetylation of ACSL4 inhibits F-box protein 10 (FBXO10)-mediated K48-linked ubiquitination, resulting in enhanced protein stability of ACSL4. This study reveals the novel regulatory mechanism of ferroptosis-related protein from the perspective of protein acetylation, and provides a novel method for the radiosensitivity of NPC.